Penerapan Interior Branding pada Hotel Yello - Astri Indrawati Gunawan (Intra, 2017)
The development of entertainment and tourism in Surabaya has lead to increasing of tourist arrival. This condition makes hotel businesses flourishing. The 3 star hotel is currently the best-selling hotel due to adequate facilities at current economic level. To cope with the competition, many 3 star hotels applied branding in the interior. Interior branding is formed not only from the visual beauty, but rather to the room’s atmosphere that contains stories and unique messages to influence the perception of visitors. One of the hotel that using interior branding is Yello Hotel. This hotel which located both in Surabaya and Jakarta was chosen as the object for research because of their unique interior concept containing purpose and positive messages for the visitors. This thesis aims to find out how the application of interior branding at Yello Hotel. Whether an application with the 3 aspects of interior branding according to Kim Kuhteubl, in which: clear vision, unique story, and energy. This Kim Kuhteubl theories are also supported by other hotel interior theories. This research is a qualitative research with descriptive analysis method. Based on the results of the analysis, both Hotel Yello has applied all aspects of interior branding properly. This application is seen in the usage of shapes, colors, and materials of interior elements, organization of space, and furniture arrangement. The success of the Yello Hotel branding is supported by the visitor’s satisfaction rate while stayed at Yello Hotel. The interior branding becomes an important things in interior design, especially in hotel. By applying interior branding, visitors are expected to have good first impression to the hotel. Beside that, visitors can understand the story/message that conveyed by the hotel. The hotel’s story/message that conveyed this way will be a leverage that differentiate from the other hotel.